ETIKA JURNALISME MENURUT PERSPEKTIF ISLAM - Anti Lailatul Ikhtiar; Nadya Farah Natasya; Dinda Sakura Ali; Mas’udah Mas’udah; Novita Ramadan; Yayat Suharyat (Pusat Riset dan Inovasi Nasional, 2022)
In practice, journalism has a great influence on the news that is disseminated, the use of journalistic codes of ethics is used to guide the process of retrieving and disseminating the information collected. In this urnal examines the formulation of Islamic journalistic ethics. The rules in carrying out journalistic duties are inseparable from the teachings of Islam which are guided by the Qur'an. So far, some Journalism has made western press theory a guide to the implementation of journalistic duties rather than press theory in an Islamic perspective. Thus, the purpose of this activity is expected to add insight to readers about the implementation of journalism in accordance with Islamic law and can be applied in journalism activities. This research also used supporting documents from both several existing books and journals. The results showed that the formulation of Journalistic Ethics According to an Islamic Perspective needs to be continuously socialized in various activities, both lectures and journalistic trainings, especially on Islamic campuses.